Zatoichi at Large Based on a Short Story by Kan Shimozawa - Mori, Kazuo; Morita, Fujio; Katsu, Shintaro; Mikuni, Rentaro; Morishige, Hisaya (Criterion, 2019)
Zatoichi comes across a pregnant woman dying from sword wounds and helps deliver her baby. Her final request to him: take the boy to see his father. From here, the film evolves into one of the wilder rides in the Zatoichi series, including such quirky touches as a mysterious child who follows Ichi and pelts him with rocks, monkey performances, and an unexpectedly hilarious take on the ronin challenger. [www.criterion.com]
Keywords: Blu-Ray-Disc